A Tool for Improving Fifth Grader Listening and Speaking Skills: Interactive Balinese Shadow Puppet Comics - I Gede Wahyu Sukadana Sukadana; I Komang Sudharma Sudharma; Ketut Herya Darma Utami Utami (Universitas Pendidikan Ganesha, 2026)
Low listening and speaking skills of fifth-grade students at Elementary School in English subjects majorly caused by the lack of innovative learning media and low student engagement. The purpose of this study is to develop valid and effective Balinese Puppet-based interactive comic media to improve students' listening and speaking skills. This study is a Research and Development (R&D) project using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the trial were 24 fifth-grade students. Data collection instruments included expert validation questionnaires and tests (pre-test and post-test). The results showed that the media was declared highly feasible by material experts, media experts, and instructional design experts. The effectiveness test results indicated a significant improvement in students' skills after using the media. It can be concluded that the Balinese Puppet interactive comic media have a big potential in improving students' listening and speaking skills and is capable of providing a contextual learning experience through the integration of local culture.